2018
DOI: 10.1021/acs.cgd.8b01066
|View full text |Cite
|
Sign up to set email alerts
|

Control of Calcium Phosphate Nucleation and Transformation through Interactions of Enamelin and Amelogenin Exhibits the “Goldilocks Effect”

Abstract: Although amelogenin comprises the vast majority of the matrix that templates calcium phosphate nucleation during enamel formation, other proteins, particularly enamelin, are also known to play an important role in the formation of enamel's intricate architecture. However, there is little understanding of the interplay between amelogenin and enamelin in controlling processes of mineral nucleation and growth. Here, we used an in vitro model to investigate the impact of enamelin interaction with amelogenin on cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
50
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(55 citation statements)
references
References 73 publications
5
50
0
Order By: Relevance
“…In vitro and in vivo studies have suggested that protein assembly is the principal mechanism for controlling nucleation, growth, and organization of mineral crystals during enamel biomineralization ( Margolis et al, 2006 ; Moradian-Oldak, 2012 ). Enamel extracellular proteins may function in a cooperative or synergic manner and direct interactions or co-assembly may be a requirement for their role ( Fan et al, 2011 ; Wald et al, 2017 ; Tao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro and in vivo studies have suggested that protein assembly is the principal mechanism for controlling nucleation, growth, and organization of mineral crystals during enamel biomineralization ( Margolis et al, 2006 ; Moradian-Oldak, 2012 ). Enamel extracellular proteins may function in a cooperative or synergic manner and direct interactions or co-assembly may be a requirement for their role ( Fan et al, 2011 ; Wald et al, 2017 ; Tao et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…This could also explain the severe separation of ameloblasts from underlying matrix in mice with deleted Ambn exons 5 and 6 ( Fukumoto et al, 2004 ). Another aspect of such interactions may be related to the synergic function of these proteins in controlling mineral nucleation and growth ( Fan et al, 2011 ; Tao et al, 2018 ). The ability of Ambn C-terminal region to bind calcium has been well-documented ( Yamakoshi et al, 2001 ; Tarasevich et al, 2007 ; Zhang et al, 2011 ) suggesting Ambn’s involvement in mineralization.…”
Section: Discussionmentioning
confidence: 99%
“…3g). If adsorbed randomly with no energetic bias for adsorption next to neighbouring proteins, the expected coverage of isolated monomers for the total 2nd layer coverage seen here (23%) would be 7% 38 , which is 20 times the observed 0.35% coverage of isolated monomers ( Supplementary Fig. 12).…”
Section: Resultsmentioning
confidence: 50%
“…3, a to e and Supplementary Videos 1 to 5) revealed that ACP ((Ca 2 (HPO 4 ) 3 ) 2-) was the rst phase to form at all values of σ explored here for all ve sequences, as validated by in situ AFM and electron microscopy (Supplementary Figs. 11 to 13) and observed previously for nucleation on a number of proteins [18][19][20] . The ACP particles grew in size ( Supplementary Table S3) before transforming to ber-or plate-shaped mineral (Fig.…”
mentioning
confidence: 57%
“…To determine the mechanism and underlying energetic factors through which Amel NR drive ACP nucleation, the data on nucleation rates vs σ were analyzed using classical nucleation theory (CNT), which has been used previously to analyze heterogeneous nucleation on organic templates 18,19,[21][22][23] and has been shown to effectively describe ACP nucleation kinetics 18 . CNT predicts that the heterogeneous nucleation rate (J o ) varies exponentially with the effective interfacial energy (α ACP ) and σ ACP according to:…”
mentioning
confidence: 99%